Recycled polyester resin composition and laminated recycled polyester film
Patent Information
- Application Number
- JP2024148628
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-14
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-27
AI Technical Summary
【0013】 本発明のポリエステル樹脂は色調が良好であり、フィルムへ加工した際も異物が少なく、かつ機能層との密着性が良好なフィルムを提供することができる。
Smart Images

Figure 2025042590000001 
Figure 2025042590000002 
Figure 2025042590000003
Abstract
Description
[Technical field]
[0001] The present invention relates to recycled polyester resins and laminated recycled polyester films. [Background technology]
[0002] Polyester resins are excellent in mechanical properties, thermal properties, chemical resistance, electrical properties, and moldability, and are used in various applications. Among polyesters, polyethylene terephthalate (hereinafter referred to as PET) is particularly used in various applications due to its excellent mechanical properties, thermal properties, chemical resistance, moldability, and ease of surface control. PET films made from PET, especially biaxially oriented PET films, are used as various industrial materials such as base films for coated magnetic recording tapes and materials for capacitors due to their excellent mechanical properties, thermal properties, dimensional stability, and surface properties. Many of these polyester films have functional layers with various functions laminated on one or both sides of the surface.
[0003] As the polyester film is used in various applications, the amount of waste and used products generated is also increasing, which leads to the deterioration of the global environment. In order to solve this problem and recycle the polyester film, it is preferable to remove the functional layer from the polyester film and reuse it as a polyester film.
[0004] As such a technique, for example, Patent Document 1 proposes a method in which a polyester film having a coating film is brought into contact with an alkaline processing liquid for 5 to 1000 minutes to remove the coating film.
[0005] Patent Document 2 discloses a method for removing a coating film by contacting a polyester film having a coating film with a 20 to 60 mass % alkaline processing liquid heated to a temperature of 90 to 140°C, thereby shortening the contact time with the alkaline processing liquid.
[0006] Patent Document 3 discloses a method for removing a coating film by contacting a polyester film having a coating film with an alkaline processing liquid containing 30% by mass or more of alcohol, thereby shortening the contact time with the alkaline processing liquid.
[0007] Patent document 4 presents a method in which a soluble resin layer is provided on the film surface of a laminated film, and a functional layer is laminated on top of that, thereby allowing the functional layer to be easily removed by dissolving the soluble resin layer with a cleaning agent. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Japanese Patent Application Publication No. 8-146560 [Patent Document 2] JP 2020-90094 A [Patent Document 3] JP 2009-291690 A [Patent Document 4] Patent Publication No. 2023-020615 Summary of the Invention [Problem to be solved by the invention]
[0009] However, the above proposal had the problem that when a recycled polyester resin was obtained from the polyester film substrate after removing the functional layer, and a functional layer was laminated onto the obtained recycled polyester resin to reuse it as a polyester film, the adhesion between the polyester film and the functional layer was poor.
[0010] The present invention has been made in consideration of the above, and aims to provide a recycled polyester resin and a laminated recycled polyester film that have good adhesion between the polyester film and the functional layer when the polyester resin obtained from the polyester film substrate after removing the functional layer is reused as a polyester film. [Means for solving the problem]
[0011] As a result of intensive research to solve the above-mentioned problems, the inventors have discovered that by setting the amount of silicon and alkali metal contained in the recycled polyester resin within specific ranges, the recycled polyester resin obtained from the polyester base film after functional layer removal can be processed again into a film that has good color tone, little foreign matter, and good adhesion to the functional layer.
[0012] The present invention is configured as follows. (1) Recycled polyester resin that meets the following requirements 1) and / or 2). 1) The Si content of the recycled polyester resin is 0.5 mmol% or more and 27.3 mmol% or less. 2) The amount of alkali metal in the recycled polyester resin is 0.5 mmol% or more and 20.0 mmol% or less. (2) The recycled polyester resin according to (1) above, which is produced by removing a release layer mainly made of silicone from a polyester film. (3) The recycled polyester resin according to (2) above, wherein the functional layer is removed by a roll-to-roll method. (4) A laminated recycled polyester film consisting of at least three layers, including a polyester layer A (A layer) having a film surface, and a C layer having no film surface, which contains a recycled polyester resin satisfying the following requirements 3) and / or 4). 3) The Si content of the recycled polyester resin is 0.5 mmol% or more and 27.3 mmol% or less. 4) The amount of alkali metal in the recycled polyester resin is 0.5 mmol% or more and 20.0 mmol% or less. (5) A laminated recycled polyester film in which the recycled polyester resin according to (4) is produced by removing a release layer mainly composed of silicone from a polyester film. (6) A laminated recycled polyester film, in which the release layer according to (5) is removed by a roll-to-roll method. Effect of the Invention
[0013] The polyester resin of the present invention has a good color tone, and when processed into a film, it is possible to provide a film with little foreign matter and with good adhesion to a functional layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below. In this specification, the use of "to" indicating a numerical range means that the numerical values before and after it are included as the lower limit and upper limit, unless otherwise specified.
[0015] [Polyester Resin] The polyester resin in the present invention is not particularly limited, but examples thereof include polyesters obtained by polycondensation of a dicarboxylic acid component and a diol component.
[0016] Examples of the dicarboxylic acid component include various dicarboxylic acid components such as aromatic dicarboxylic acids, linear aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, etc. Specific examples include terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, and phthalic acid.
[0017] The diol component is preferably an aliphatic glycol, such as ethylene glycol, diethylene glycol, propylene glycol, butylene glycol, 1,4-cyclohexanedimethanol, neopentyl glycol, etc. In addition to diols, polyfunctional alcohols such as trimethylolpropane and pentaerythritol can also be used.
[0018] In addition, other components may be copolymerized within the scope of the present invention, and examples of such components include diol components such as diethylene glycol, propylene glycol, neopentyl glycol, polyalkylene glycol, p-xylylene glycol, 1,4-cyclohexanedimethanol, and 5-sodium sulforesorcin, polyfunctional alcohol components such as trimethylolpropane and pentaerythritol, dicarboxylic acid components such as adipic acid, sebacic acid, phthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, and 5-sodium sulfoisophthalic acid, polyfunctional dicarboxylic acid components such as trimellitic acid and pyromellitic acid, and oxycarboxylic acid components such as p-oxyethoxybenzoic acid. In addition, the polyester may contain a third component other than the dicarboxylic acid component and the diol component as a copolymer component.
[0019] Specific examples of polyesters include polyethylene terephthalate, polyethylene-2,6-naphthalate, polybutylene terephthalate, polybutylene-2,6-naphthalate, etc., of which polyethylene terephthalate is preferred. These may also be copolymer polyesters.
[0020] In addition, various additives may be contained in the composition by a conventional method, so long as the object of the present invention is not impaired. Examples of the additives include an end-capping agent, an antioxidant, a flame retardant, a fluorescent whitening agent, a matting agent, a plasticizer, and an antifoaming agent.
[0021] The polyester resin of the present invention contains silicon atoms (elements) of 0.5 mmol% or more and 27.3 mmol% or less. If the silicon content is less than 0.5 mmol%, the adhesion of the functional layer to the polyester film using the polyester resin of the present invention is deteriorated. On the other hand, if the silicon content exceeds 27.3 mmol%, the amount of foreign matter in the film using the polyester resin of the present invention increases. By setting the content within the above range, the amount of foreign matter is reduced and the adhesion of the functional layer when made into a film is good. The mechanism by which the adhesion of the functional layer when made into a film is good is not clear, but is presumed to be as follows. The remaining silicon maintains the structure derived from the functional layer that was removed. It is presumed that the adhesion is good when a functional layer having a similar structure is applied by the remaining silicon acting as an intermediary.
[0022] The polyester resin of the present invention contains an alkali metal of 0.5 mmol% or more and 20.0 mmol% or less. More preferably, it is 1.0 mmol% or more and 17.0 mmol% or less, and particularly preferably, it is 1.7 mmol% or more and 15.0 mmol% or less. If the alkali metal is less than 0.5 mmol%, the adhesion of the functional layer to the polyester film using the polyester resin of the present invention is deteriorated. On the other hand, if the alkali metal is more than 20.0 mmol%, the color tone of the polyester resin of the present invention and the film using it is deteriorated. By setting it in the above range, the color tone is good and the adhesion of the functional layer when made into a film is good. As the alkali metal, sodium and potassium are preferable.
[0023] [Method for producing polyester resin] The polyester resin of the present invention is preferably a recycled polyester resin. In this specification, recycled polyester refers to polyester obtained by depolymerizing and repolymerizing polyester recovered after use, so-called chemical recycled polyester, or polyester obtained by sorting and pulverizing polyester recovered after use, melting it after washing, and re-pelletizing it, so-called material recycled polyester.
[0024] The recycled polyester resin is preferably a material recycled polyester, and more preferably a recycled polyester resin obtained by removing the release layer from a polyester film substrate including a polyester film and at least one release layer made of silicone provided on at least a portion of the polyester film, recovering the polyester film, and pelletizing the polyester film using an extruder or the like.
[0025] The method for removing the release layer from the polyester film substrate is not particularly limited, but examples thereof include a roll-to-roll method (hereinafter also abbreviated as R to R method) in which a polyester film substrate wound in a roll is continuously transported, the release layer is removed from the polyester film substrate during transport, the polyester film is wound again in a roll state, recovered, and pelletized, and a batch method in which the polyester film substrate is made into flakes, the release layer is removed using a cleaning tank equipped with an agitator, and the flakes are recovered and pelletized. Since the batch method may result in uneven processing due to overlapping of flakes, the R to R method, which provides uniform processing, is preferred.
[0026] [Polyester film] The polyester film may be commercially available, or may be produced by the following method. For example, a polyester resin is vacuum dried, fed to an extruder, melted at 260 to 300°C, extruded into a sheet from a T-shaped die, and wound around a mirror-finished casting drum with a surface temperature of 10 to 60°C using an electrostatic casting method, and cooled and solidified to produce an unstretched polyester film. The unstretched polyester film is stretched 2.5 to 5 times in the longitudinal direction between rolls heated to 70 to 130°C. The film is then continuously stretched 2.5 to 5 times in the width direction in a hot air zone heated to 70 to 150°C, and then introduced into a heat treatment zone at 190 to 240°C, where it is heat-treated for 5 to 40 seconds, and passed through a cooling zone at 100 to 200°C to complete the crystal orientation, thereby obtaining a polyester film. During the heat treatment, a relaxation treatment of 0.1 to 12% may be performed in the width direction or longitudinal direction as necessary.
[0027] The thickness of the polyester film is not particularly limited, but is preferably 5 μm to 500 μm in consideration of handleability such as strength, rigidity, etc. The thickness of the polyester film is more preferably 10 μm to 200 μm, and particularly preferably 20 μm to 100 μm.
[0028] [Release layer made of silicone] The polyester film has at least one release layer on at least a part of the polyester film substrate. In the polyester film, the release layer may be present on at least one side of the polyester film, and may be present on both sides. Furthermore, in the polyester film, the release layer may be included alone, or other functional layers may be laminated. Here, the functional layer is a layer that can impart various functions to the polyester film, and examples of such layers include an adhesive layer, a hard coat layer, an easy-adhesion layer, and an antistatic layer. In addition, the release layer and the functional layer may have not only a single function but also multiple functions.
[0029] The resin constituting the release layer is preferably a silicone resin such as polydimethylsiloxane, etc. In addition, amino resins such as melamine resins and urea resins, acrylic resins, epoxy resins, alkyd resins, etc. may be used in combination.
[0030] The resin constituting the adhesive layer includes an adhesive that is generally used in adhesive layers. The type of the adhesive is not particularly limited, and examples thereof include acrylic adhesives, rubber adhesives, polyurethane adhesives, and silicone adhesives. The adhesive layer may further contain a tackifier (tackifier resin).
[0031] The resin constituting the hard coat layer is not particularly limited as long as it is a resin generally used in hard coat layers, and examples thereof include acrylic resins, urethane resins, epoxy resins, etc. These resins may be used alone or in combination of two or more kinds.
[0032] The resin constituting the easy-adhesion layer is not particularly limited as long as it is a resin generally used for easy-adhesion layers, and examples thereof include polyester resins, acrylic resins, polycarbonate resins, polyurethane resins, polyvinyl alcohol resins, polyamide resins, polyvinyl acetate resins, etc. These resins may be used alone or in combination of two or more kinds.
[0033] The resin constituting the antistatic layer is not particularly limited as long as it is a resin generally used for antistatic layers. The antistatic layer preferably further contains an antistatic agent. Examples of the antistatic agent include nonionic, cationic, anionic or amphoteric surfactants (conductive polymers such as polypyrrole and polyaniline, metal oxide fillers, carbonaceous materials, etc.). These antistatic agents may be used alone or in combination of two or more.
[0034] The method for forming a functional layer on a polyester-based film substrate is not particularly limited, but for example, the functional layer can be formed on a polyester-based film using a reverse coating method, a gravure coating method, a rod coating method, a bar coating method, a wire bar coating method, a die coating method, a spray coating method, or the like.
[0035] The thickness of the release layer (when multiple functional layers are present, the total thickness of these layers) is preferably 0.005 μm or more and 50 μm or less. In order to effectively exert a predetermined function, the thickness is more preferably 0.01 μm or more. On the other hand, if the thickness of the release layer is too thick, it may take a long time to remove the release layer.
[0036] [Method of Removing Release Layer] The release layer can be removed by bringing an alkaline treatment liquid into contact with at least the surface of the polyester film substrate having the release layer.
[0037] [Step of Contacting with Alkaline Processing Liquid] The alkaline treatment liquid may be a solution in which an alkaline substance is dissolved. The alkaline substance is not particularly limited, but may be, for example, an inorganic alkaline agent such as sodium hydroxide, potassium hydroxide, ammonium hydroxide, lithium hydroxide; sodium silicate, potassium silicate, ammonium silicate; sodium dibasic phosphate, potassium dibasic phosphate, ammonium dibasic phosphate; sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate; sodium carbonate, potassium carbonate, ammonium carbonate; sodium hydrogen carbonate, potassium hydrogen carbonate, ammonium hydrogen carbonate; sodium borate, potassium borate, ammonium borate, etc. Among these, alkali metal hydroxide is preferred, and sodium hydroxide and potassium hydroxide are more preferred. The alkaline substances may be used alone or in combination of two or more.
[0038] The concentration of the alkaline substance in the alkaline processing liquid is preferably 1% by mass or more and 15% by mass or less. By setting the concentration of the alkaline substance in this range, the silicon and alkali metal in the polyester resin of the present invention will be in the above-mentioned content. If the concentration of the alkaline substance is lower than 1% by mass, the amount of alkali metal in the polyester resin will decrease, and the adhesion of the functional layer to the polyester-based film substrate using the polyester resin of the present invention will deteriorate. On the other hand, if the concentration of the alkaline substance is higher than 15% by mass, the amount of alkali metal in the polyester resin will increase, and there is a risk of the color tone of the polyester resin of the present invention and the film using it being deteriorated.
[0039] The solvent for dissolving the alkaline substance is not particularly limited, but may be, for example, water.
[0040] The alkaline processing liquid may contain a surfactant or ultrafine bubbles as an auxiliary agent to prevent reattachment of the removed release layer and to increase the efficiency of removing the release layer. The surfactant is not particularly limited, and examples thereof include nonionic surfactants, cationic surfactants, and anionic surfactants. The surfactants may be used alone or in combination of two or more kinds.
[0041] Examples of the nonionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene alkylaryl ethers, polyoxyethylene fatty acid esters, and polyoxyethylene sorbitan fatty acid esters.
[0042] Examples of the cationic surfactant include alkylpyridinium chloride, alkyltrimethylammonium chloride, dialkyldimethylammonium chloride, and alkyldimethylbenzylammonium chloride.
[0043] Examples of the anionic surfactant include sodium alkyl sulfate, sodium alkylbenzene sulfonate, sodium dialkyl succinate sulfonate, sodium alkyl diphenyl ether disulfonate, sodium polyoxyethylene alkyl ether sulfate, and sodium polyoxyethylene alkyl phenyl ether sulfate.
[0044] The alkaline processing liquid may contain other additives, such as antioxidants, pH adjusters, and antifoaming agents, provided that the additives do not impair the effects of the present invention.
[0045] The temperature of the alkaline treatment liquid is preferably less than 100°C, more preferably 65°C or more and less than 100°C, and even more preferably 65 to 95°C. When the temperature of the alkaline treatment liquid is 65°C or more, it is preferable because it does not cause any change in the physicochemical properties of the polyester film and can obtain a high-quality polyester film with few impurities without spending excessive time. In addition, by making the temperature of the alkaline treatment liquid less than 100°C, it is possible to achieve the above at normal pressure, preventing the equipment from becoming large-sized, and suppressing the occurrence of hydrolysis or dissolution of the polyester film due to heating.
[0046] The contact time between the alkaline treatment liquid and the polyester film is preferably more than 30 seconds and less than 1000 seconds, more preferably more than 30 seconds and 600 seconds or less, and even more preferably more than 30 seconds and 120 seconds or less. By setting the contact time in this range, the silicon and alkali metal in the polyester resin of the present invention will be the above-mentioned content. If the contact time is too long, the amount of alkali metal in the polyester resin increases, and there is a risk that the color tone of the polyester resin of the present invention and the film using it will deteriorate. The contact time with the alkaline treatment liquid is sufficient if the release layer can be sufficiently dissolved and swollen, and if the contact time is too short, there is a risk that the release layer cannot be sufficiently removed, the amount of Si in the polyester resin increases, and there is a risk that the film using the polyester resin of the present invention will have an increased amount of foreign matter.
[0047] [Step of bringing the polyester film into contact with a surfactant, an alcohol, or an aqueous solution containing a surfactant or an alcohol]
[0048] When removing the release layer from the polyester film, a step of bringing a surfactant, alcohol, or an aqueous solution of a surfactant or alcohol into contact with at least the release layer of the polyester film may be included before the step of bringing the polyester film into contact with the alkaline treatment liquid. The surface of the polyester film is hydrophilized by bringing the surfactant, alcohol, or an aqueous solution of a surfactant or alcohol into contact with the release layer of the polyester film. By bringing the surface of the polyester film into contact with the alkaline treatment liquid in a state where the surface of the polyester film has been hydrophilized in advance, the penetration of the alkaline treatment liquid is promoted, and the release layer can be easily and efficiently removed from the polyester film in a short time.
[0049] The method of contacting the surfactant, alcohol, or aqueous solution of a surfactant or alcohol is not particularly limited as long as at least the surface of the polyester film having the release layer can be contacted with the liquid. For example, the polyester film is immersed in a cleaning tank containing a surfactant, alcohol, or aqueous solution of a surfactant or alcohol, coated, or sprayed. Among these, the immersion method is preferred from the viewpoint of the permeability of the surfactant, alcohol, or aqueous solution of a surfactant or alcohol into the release layer.
[0050] The alcohol is not particularly limited, and may be a monohydric alcohol or a polyhydric alcohol, and may be a lower alcohol or a higher alcohol.
[0051] Examples of monohydric alcohols include methanol, ethanol, propanol, butanol, pentanol, hexanol, heptanol, octanol, nonylnol, decylnol, undecylnol, dodecylnol, methoxyethanol, methoxypropanol, methoxybutanol, methoxyethoxyethanol, ethoxyethanol, ethoxyethoxyethanol, ethoxypropanol, ethoxybutanol, butoxyethanol, butoxypropanol, and butoxybutanol.
[0052] Examples of polyhydric alcohols include ethylene glycol, propylene glycol, diethylene glycol, 1,4-butanediol, glycerin, and polyoxyalkylene polyols.
[0053] Among these, monohydric lower alcohols such as methanol, ethanol, 1-propanol (normal propanol), and 2-propanol (isopropanol) are more preferred, at least one selected from the group consisting of methanol, ethanol, 1-propanol, and 2-propanol is even more preferred, and methanol and ethanol are particularly preferred. The alcohols may be used alone or in combination of two or more.
[0054] The concentration of the alcohol or the aqueous solution in which the alcohol is dissolved is preferably 0.1% by mass to 100% by mass, and the lower limit is more preferably 30% by mass or more. If the alcohol concentration is too low, there is a risk that the release layer cannot be sufficiently removed. If the alcohol or the aqueous solution in which the alcohol is dissolved is 30% by mass or more, a sufficient effect of removing the release layer can be obtained.
[0055] The temperature of the alcohol or the aqueous solution containing the alcohol may be adjusted depending on the alcohol used, but is preferably 50° C. or less, and more preferably room temperature of 5 to 30° C. If the temperature of the alcohol or the aqueous solution containing the alcohol is too high, the alcohol may boil. If the temperature of the alcohol or the aqueous solution containing the alcohol is 50° C. or less, the alcohol is below the boiling point, and the release layer removal effect is promoted.
[0056] The surfactant is not particularly limited, but may be at least one surfactant selected from the group consisting of nonionic surfactants, cationic surfactants, and anionic surfactants. In particular, nonionic surfactants are preferred. The surfactants may be used alone or in combination of two or more.
[0057] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkylphenol ethers such as polyoxyethylene octylphenol ether and polyoxyethylene nonylphenol ether; polyoxyethylene alkylaryl ethers; polyoxyethylene fatty acid esters such as polyethylene glycol monolaurate; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan tristearate, sorbitan monooleate, and sorbitan trioleate; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan moreoleate, and polyoxyethylene sorbitan trioleate; and glycerin fatty acid esters such as stearic acid monoglyceride.
[0058] Examples of the cationic surfactant include alkylpyridinium chloride, alkyltrimethylammonium chloride, dialkyldimethylammonium chloride, and alkyldimethylbenzylammonium chloride.
[0059] Examples of the anionic surfactant include sodium alkyl sulfate, sodium alkylbenzene sulfonate, sodium dialkyl succinate sulfonate, sodium alkyl diphenyl ether disulfonate, sodium polyoxyethylene alkyl ether sulfate, and sodium polyoxyethylene alkyl phenyl ether sulfate.
[0060] The concentration of the surfactant or the aqueous solution in which the surfactant is dissolved is preferably 0.00001% by mass to 100% by mass, more preferably 0.0001% by mass to 100% by mass, further preferably 0.001% by mass to 50% by mass, and particularly preferably 0.01% by mass to 1% by mass. If the surfactant concentration is too low, there is a risk that the release layer cannot be sufficiently removed. If the surfactant or the aqueous solution in which the surfactant is dissolved is 0.00001% by mass to 100% by mass, it is preferable because a sufficient release layer removal effect can be obtained.
[0061] The temperature of the surfactant or the aqueous solution in which the surfactant is dissolved may be adjusted depending on the surfactant used, but is preferably 50° C. or lower. If the temperature of the surfactant or the aqueous solution in which the surfactant is dissolved is 50° C. or lower, the surfactant can be concentrated to a high level, which promotes the removal effect of the release layer. Note that non-ionic surfactants do not dissolve in water if the temperature is too high, so it is preferable to treat them at a temperature below the cloud point of the surfactant.
[0062] The contact time between the polyester film and the surfactant, alcohol, or the aqueous solution in which the surfactant or alcohol is dissolved is preferably within 120 seconds, more preferably 0.001 to 60 seconds, even more preferably 0.001 to 10 seconds, and particularly preferably 0.1 to 10 seconds. If the contact time with the polyester film is too short, the release layer may not be sufficiently removed, and if the contact time is too long, the size of the device may become large, resulting in poor economic efficiency and operability. If the contact time with the polyester film is within 120 seconds, the economic efficiency and operability are good, and the removal effect of the release layer can be enhanced.
[0063] The surfactant, alcohol, or the aqueous solution containing the surfactant or the alcohol may contain ultra-fine bubbles as an auxiliary agent to enhance the efficiency of removing the release layer. The alcohol or the aqueous solution containing the alcohol may contain the surfactant, and the surfactant or the aqueous solution containing the surfactant may contain the alcohol.
[0064] [Step of surface modification of polyester film] When removing the release layer from the polyester film, a step of performing a surface modification treatment on the surface of the release layer in the polyester film may be included for the purpose of increasing the affinity with the alkaline treatment liquid before the step of contacting the polyester film with the alkaline treatment liquid. The surface modification treatment is not particularly limited, and a known method can be adopted, for example, corona discharge treatment, plasma treatment, glow discharge treatment, flame treatment, ultraviolet treatment, etc., and it is preferable to perform at least one treatment selected from the group consisting of these.
[0065] The surface modification treatment may be carried out before the step of bringing the polyester film into contact with an alkaline treatment liquid. However, in order to increase the affinity with a surfactant, alcohol, or an aqueous solution containing a surfactant or alcohol, it is more preferable to carry out the surface modification treatment before the step of bringing the polyester film into contact with a surfactant, alcohol, or an aqueous solution containing a surfactant or alcohol.
[0066] If an analysis using X-ray photoelectron spectroscopy after the surface modification treatment shows that the proportion of C-C bonds and C-H bonds has decreased by 0.1% or more, the effect of increasing the affinity with a surfactant, alcohol, or an aqueous solution containing a surfactant or alcohol, or an alkaline treatment liquid can be obtained.
[0067] For corona discharge treatment, the treatment intensity is 10 to 1000 Wmin / m 2 More than 20 to 200 Wmin / m is preferable. 2 More preferably, 40 to 120 Wmin / m 2 If the treatment intensity is too high, the polyester film tends to be easily damaged, whereas if the treatment intensity is too low, the contact time with the alkaline treatment liquid becomes long, the amount of alkali metal in the polyester resin increases, and the color tone of the polyester resin of the present invention and the film using the same may deteriorate. The power density of the corona discharger used is preferably 4 to 20 W / cm. 2If so, the surface treatment can be performed uniformly.
[0068] For UV treatment, the irradiation intensity is 0.5 to 40 mW / cm 2 is preferably 10 to 40 mW / cm 2 More preferably, 15 to 40 mW / cm 2 is more preferable. If the irradiation intensity is too high, the polyester film tends to be easily damaged, and if the irradiation intensity is too weak, the contact time with the alkaline processing liquid becomes long, the amount of alkali metal in the polyester resin increases, and the color tone of the polyester resin of the present invention and the film using it may deteriorate. The irradiation time of ultraviolet light is preferably 3 to 210 seconds, more preferably 30 to 100 seconds, and even more preferably 50 to 70 seconds. If the irradiation time of ultraviolet light is too long, the size of the device needs to be increased, which increases the manufacturing cost and the polyester film tends to be easily damaged. If the irradiation time of ultraviolet light is too short, the release layer may not be sufficiently removed, the amount of Si in the polyester resin may increase, and the amount of foreign matter in the film using the polyester resin of the present invention may increase. In addition, it is preferable to use an electromagnetic wave of 10 to 400 nm, that is, invisible light shorter than visible light and longer than soft X-rays. Examples of sources of ultraviolet rays include known lamps such as ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arc lamps, and metal halide lamps, with low pressure mercury lamps being preferred.
[0069] [Step of performing water washing treatment] When removing the release layer from the polyester film, it is preferable to include a step of washing the polyester film with water after the step of contacting the polyester film with an alkaline treatment liquid. The washing with water is performed to remove the release layer remaining on the polyester film and to make the alkali metal remaining on the polyester film after the treatment within the range of the present application.
[0070] The temperature for the water washing treatment is not particularly limited, but for example, washing with warm water of about 40° C. to 100° C. will more effectively exhibit the above effects.
[0071] Examples of the method of washing with water include a method of spraying water onto the polyester film from which the release layer has been removed, a method of immersing the polyester film in a water tank, etc. During the water washing treatment, physical washing using a roll brush, microbubbles, water flow, etc. may be performed.
[0072] The time for the water washing treatment is preferably 0.1 seconds to 20 minutes, and more preferably 1 second to 25 minutes. By setting the water washing time within this range, the silicon and alkali metals in the polyester resin of the present invention will have the above-mentioned contents. If the water washing time is too short, there is a risk that the release layer cannot be sufficiently removed, the amount of Si in the polyester resin increases, and the amount of foreign matter in the film using the polyester resin of the present invention may increase. If the water washing time is too long, the alkaline treatment liquid is removed, so the amount of alkali metals in the polyester resin decreases, and the adhesion of the functional layer to the polyester film using the polyester resin of the present invention deteriorates.
[0073] [Step of performing drying treatment] When removing the release layer from the polyester film, it is preferable to carry out a drying treatment after the step of washing the polyester film with water in order to remove water remaining on the polyester film.
[0074] The drying time is preferably 10 seconds or more and 5 minutes or less. When the drying time is 10 seconds or more, the drying is sufficient and blocking can be suppressed. It is more preferably 30 seconds or more. In addition, when the drying time is 5 minutes or less, deformation of the polyester film can be prevented.
[0075] The drying method is not particularly limited, and examples thereof include hot air drying in which hot air is blown onto the substrate, and heat drying in which a non-contact heater is used.
[0076] [Multiple treatments] The step of contacting the polyester film with the alkaline treatment liquid, the step of contacting the polyester film with a surfactant, an alcohol, or an aqueous solution containing a surfactant or an alcohol, and the step of surface modification of the polyester film may be carried out multiple times. By carrying out these treatments multiple times, the polyester film can be treated in a short time without being damaged, such as by a decrease in intrinsic viscosity.
[0077] [Pelletizing process] The recovered polyester film is preferably pelletized to produce the polyester resin of the present invention.
[0078] The method for pelletizing is not particularly limited, and may be, for example, a method in which the recovered polyester film is pulverized, fed into an extruder, melted, and pelletized.
[0079] [Molding and applications of recycled polyester resin] The recycled polyester resin of the present invention is produced by extrusion molding.
[0080] The polyester product to which the present invention is applied is not particularly limited, and can be used for ordinary polyester applications, such as polyester films, PET bottles, polyester fibers, polyester sheets, polyester containers, etc. Specifically, it can be used as a polyester film, for example.
[0081] [Laminated recycled polyester film using recycled polyester resin] The recycled polyester film of the present invention is preferably a laminated polyester film having three or more layers. Among them, it is preferable that the recycled polyester resin of the present invention is contained in a layer that does not have a film surface. Even if the recycled polyester resin of the present invention is contained in the inner layer of the film, it is possible to obtain a laminated recycled polyester film having good adhesion with the functional layer. The mechanism by which the adhesion is good even in the inner layer of the film is not clear, but it is presumed as follows. Since the affinity between polyester and silicon derived from the functional layer is not high, it is thought that silicon seeps out to the surface layer. It is presumed that the adhesion is good when a functional layer having a structure similar to that of the seeped out silicon is applied by the intermediation of the seeped out silicon.
[0082] The thickness of the laminated recycled polyester film is not particularly limited, but can usually be appropriately set within the range of 10 to 50 μm. In addition, a functional layer can be formed as necessary. Examples of the functional layer include a release layer, an adhesive layer, a hard coat layer, an easy-adhesion layer, and an antistatic layer. In addition, the laminated recycled polyester film can be recovered again, the functional layer can be removed, and the film can be extruded to produce a polyester product.
[0083] The polyester products produced from the recycled laminated polyester film are not particularly limited, and can be used for ordinary polyester applications, such as the polyester films, PET bottles, polyester fibers, polyester sheets, and polyester containers mentioned above. EXAMPLES
[0084] The present invention will be described in more detail below with reference to examples and comparative examples. The described embodiments are not intended to be limiting.
[0085] (Evaluation method) (1) Silicon content of polyester resin Quantitative analysis was performed using alkali fusion, nitric acid dissolution, and inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0086] (2) Amount of alkali metal in polyester resin 1 g of polyester resin was placed on a platinum dish and completely incinerated at 700°C for 1.5 hours. The incinerated material was then dissolved in 20 mL of 0.25 N hydrochloric acid solution, and pure water was added to make the solution 0.1 N hydrochloric acid. This was used as a measurement sample, and quantification was performed using atomic absorption spectrometry (polarized Zeeman atomic absorption spectrometer model 180-80, manufactured by Hitachi, Ltd., flame: acetylene-air).
[0087] (3) Color tone of polyester resin The polyester resin was filled into a cylindrical powder measurement cell, and the b value was measured using a reflection method with a color difference meter (SM color meter SM-T) manufactured by Suga Test Instruments Co., Ltd., n = 3. The arithmetic mean of the measured values was taken as the color tone b value, and the color tone b value was evaluated as follows. ◎: Color tone b value is 14.5 or less ○: Color tone b value is greater than 14.5 and less than 15.0 △: Color tone b value is greater than 15.0 and less than 15.5 ×: Color tone b value is 15.5 or more.
[0088] (4) Foreign matter in polyester resin 1 g of the polyester resin composition was dissolved in 20 ml of a 60 / 40 solution of phenol / 1,1,2,2,tetrachloroethane, and filtered through filter paper. The number of black foreign particles (17 μm or larger) on the surface of the filter paper was counted under a stereomicroscope (60x). ◎: The number of foreign objects is less than 5. ○: 5 or more but less than 10 foreign objects △: 10 or more but less than 15 foreign objects ×: 15 or more foreign objects.
[0089] (5) Adhesion of the release layer of recycled polyester film The adhesion of the release layer is evaluated by the following methods a,b,c. a. Manufacturing of recycled polyester film The polyester resin of the present invention was dried at 150° C. for 3 hours, fed to an extruder, melt-extruded at 285° C., and cast onto an electrostatically charged casting drum at 20° C. to obtain an unstretched sheet. This unstretched sheet was stretched 3.1 times in the longitudinal direction by a stretching roll heated to 90° C., then stretched 3.7 times in the transverse direction at 120° C. by a tenter-type stretching machine, and then heat-set at 230° C. and wound up on a roll.
[0090] b. Application of release layer A coating solution containing a crosslinking primer layer (manufactured by Dow Corning Toray Silicone Co., Ltd. under the trade name BY24-846) adjusted to a solid content of 1 mass% was applied to the surface of the polyester film, dried, and coated with a gravure coater so that the coating thickness after drying would be 0.1 μm, and dried and cured at 100° C. for 20 seconds. Within one hour, a coating solution containing 100 parts by mass of an addition reaction type silicone resin (manufactured by Dow Corning Toray Silicone Co., Ltd. under the trade name LTC750A) and 2 parts by mass of a platinum catalyst (manufactured by Dow Corning Toray Silicone Co., Ltd. under the trade name SRX212) adjusted to a solid content of 5 mass% was applied with a gravure coater so that the coating thickness after drying would be 0.1 μm, dried and cured at 120° C. for 30 seconds, and then wound up to obtain a release film.
[0091] c. Adhesion evaluation A checkerboard test was carried out on 100 squares from the release layer side according to JIS K5400 8.5 (1999). The same test was carried out on 10 places, and the average value of the squares that peeled off was taken as the adhesion to the release layer and was evaluated as follows. ◎: The average number of peeled masses is 10 or less 〇: The average number of peeled masses is between 11 and 20 △: The average number of peeled masses is between 21 and 25. ×: The average number of peeled masses is 26 or more.
[0092] d. Evaluation of adhesion variation In a checkerboard test of 100 squares in 10 locations to evaluate adhesion, the difference between the maximum and minimum numbers of peeled squares was taken as the variation in adhesion and was evaluated as follows: 〇: The difference between the maximum and minimum number of peeled squares is 3 or less ×: The difference between the maximum and minimum number of peeled squares is 4 or more.
[0093] (6) Adhesion of release layer of laminated recycled polyester film The adhesion of the release layer is evaluated by the following methods a,b,c.
[0094] a. Preparation and mixing of laminated recycled polyester film raw materials (Preparation of polyester A) Esterification reaction was carried out with 86.5 parts of terephthalic acid and 37.1 parts of ethylene glycol at 255° C. while distilling off water. After the esterification reaction was completed, 0.02 parts of trimethyl phosphate, 0.06 parts of magnesium acetate, 0.01 parts of lithium acetate, and 0.0085 parts of antimony trioxide were added, and the mixture was heated to 290° C. under reduced pressure to carry out a polycondensation reaction, thereby obtaining polyester pellets A having an intrinsic viscosity of 0.63 dl / g.
[0095] (Creating polyester B) An aqueous slurry of divinylbenzene / styrene copolymer crosslinked particles having a volume average particle diameter of 0.3 μm was added to polyester A using a vented twin-screw kneader to obtain polyester B containing 0.2% by weight of divinylbenzene / styrene copolymer crosslinked particles having a volume average particle diameter of 0.3 μm relative to the polyester.
[0096] (Polyester pellet blending) The polyester pellets fed to the extruder for each of the layers A and B were mixed in the following ratios. The ratios shown below are mass ratios (unit: mass%) to the polyester pellets constituting each layer.
[0097] A layer Polyester A: 70.0 Polyester B: 30.0
[0098] B layer Polyester resin of the present invention: 100.0
[0099] b. Manufacturing of laminated recycled polyester film The raw materials prepared for each layer were mixed in a blender, and then the raw materials for layer A were fed to a vented twin-screw extruder for layer A, and the raw materials for layer B were dried under reduced pressure at 160°C for 8 hours and fed to a single-screw extruder for layer B. Layer A was filtered through a high-precision filter that captures 95% or more of foreign matter of 5 μm or more. Layer B was melt-extruded at 275°C in a tandem extruder, filtered through a high-precision filter that captures 95% or more of foreign matter of 5 μm or more, and then layer A and layer B were joined and laminated in a joining block to form a three-layer laminate consisting of layer A, layer B, and layer A. After that, the film was wrapped around a casting drum with a surface temperature of 25°C using an electrostatic application casting method in which electrostatic application is applied to the entire width of the unstretched film through a slit die maintained at 285°C, and cooled and solidified to obtain an unstretched laminated film. Sequential stretching was performed on this unstretched laminated film in the longitudinal and transverse directions. First, the film was stretched in the longitudinal direction, transported at 105°C, and then stretched 3.8 times in the longitudinal direction at 120°C to obtain a uniaxially stretched film. This uniaxially stretched film was stretched 4.0 times in the transverse direction at 115°C in a stenter, then heat-set at 230°C and wound up on a roll. The thickness ratio of the laminated recycled polyester film was A layer / B layer / A layer = 1.5 μm / 22 μm / 1.5 μm.
[0100] c. Application of release layer (5) Adhesion of release layer of recycled polyester film b. A release film was obtained in the same manner as in coating of the release layer.
[0101] d. Adhesion evaluation (5) The adhesion of the release layer of the recycled polyester film was evaluated in the same manner as in c. Adhesion evaluation.
[0102] (Preparation of sample films). A laminated polyester film having a release layer was prepared as a sample film as follows.
[0103] (1) Preparation of laminated polyester film with release layer A polyethylene terephthalate film (Toray Industries, Inc.'s "Lumirror" T60, thickness 38 μm, intrinsic viscosity 0.61) was prepared as a polyester film. One side of the film was coated with a 5% by mass toluene solution of a curable silicone resin (containing 100 parts of Toray Dow Corning Silicones Co., Ltd.'s LTC-350B and 0.8 parts of the same company's curing agent SRX-212) using a bar coater, and the film was heated at 100°C in a tunnel oven to produce a release film, which was then wound up.
[0104] (2) Application of ceramic slurry and conductive paste A ceramic slurry having the following composition was uniformly applied to the release layer surface of the release film using a blade coater. This was dried in a tunnel oven at 85°C to form a ceramic layer having a thickness of 20 μm on the release film. Next, a conductive paste having the following composition was screen-printed on the ceramic layer, dried at 80°C for 10 minutes to form an electrode, and then left at 20°C for 1 hour.
[0105] Ceramic Slurry Composition Ceramic powder (barium titanate): 100 parts Binder (polyvinyl butyral): 10 parts Plasticizer (dioctyl phthalate): 5 parts Solvent (toluene / isopropyl alcohol = 1 / 1 (mass ratio)): 100 parts
[0106] Conductive paste composition Ni-based powder: 90 parts Organic vehicle: 10 parts Terpineol: 30 parts.
[0107] (3) Peeling off of the ceramic layer and internal electrodes On the release film on which the ceramic layer and electrodes were formed, a 10 cm x 10 cm slit was made only in the release layer where the ceramic layer and electrodes were formed, and then the ceramic layer and the electrodes were sucked with a vacuum suction machine and peeled off from the release film to obtain a roll-shaped sample film. Note that some of the ceramic layer and electrodes that could not be peeled off were still attached to the surface of the release layer of the sample film.
[0108] [Example 1] The release layer surface of the sample film was treated with a corona discharge treatment device at a power density of 8 W / cm 2 , Processing intensity 60Wmin / m 2 The corona discharge treatment was performed at 1000°C. The corona discharge treated sample film was immersed in a 0.03% by mass aqueous solution of a nonionic surfactant ("Polyoxyethylene (10) Octylphenyl Ether" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) at room temperature of 25°C for 1 second. 1000 L of a mixed aqueous solution of 3% by mass sodium hydroxide and 0.03% by mass of a nonionic surfactant ("Polyoxyethylene (10) Octylphenyl Ether" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was heated to 80°C. The sample film was transported there and contacted with the alkaline treatment liquid for 45 seconds to remove the release layer, thereby obtaining a recovered polyester film in a roll state. The recovered polyester film was immersed in a water tank containing water for 45 seconds, and then dried in a roll by blowing hot air on it. The dried sample film was crushed, put into an extruder, melted, and pelletized to obtain a polyester resin.
[0109] [Examples 2 to 5] A polyester resin was obtained in the same manner as in Example 1, except that the contact time with the alkaline treatment liquid was set as shown in Table 1-1.
[0110] [Example 6] The release layer surface of the sample film was treated with a corona discharge treatment device at a power density of 8 W / cm 2 , Processing intensity 60Wmin / m 2The corona discharge treatment was performed at 1000 rpm. The corona discharge treated sample film was shredded with a micro cross-cut type office shredder. Then, 40 kg of the shredded film pieces were added to a cleaning tank equipped with an agitator, and 1000 L of a 0.03 mass% aqueous solution of a nonionic surfactant ("Polyoxyethylene (10) Octylphenyl Ether" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added so that all the film pieces were immersed. The agitator rotation speed was set to 200 rpm and the mixture was stirred for 1 second. After stirring, the nonionic surfactant aqueous solution was removed from the cleaning tank. Then, 1000 L of 3 mass% sodium hydroxide and 0.03 mass% nonionic surfactant were added to the cleaning tank, and the cleaning tank was heated to 85°C. The agitator rotation speed was set to 200 rpm and the sample was washed for 45 seconds. After washing, the alkaline treatment solution was removed from the cleaning tank, and then 1000 L of pure water was added to the cleaning tank, and the agitator rotation speed was set to 200 rpm and the sample was washed for 45 seconds. After washing with water, the pure water and the film pieces were taken out separately, and the film pieces were dried by blowing hot air on them. The dried film pieces were fed into an extruder, melted, and pelletized to obtain a polyester resin.
[0111] [Examples 7 to 10] A polyester resin was obtained in the same manner as in Example 6, except that the contact time with the alkaline treatment liquid was set as shown in Table 1-1.
[0112] [Examples 11 to 13] A polyester resin was obtained in the same manner as in Example 1, except that the sodium hydroxide concentration was set as shown in Table 1-1.
[0113] [Examples 14 to 16] Polyester resins were obtained in the same manner as in Example 6, except that the sodium hydroxide concentrations shown in Table 1-2 were used.
[0114] [Examples 17 to 20] A polyester resin was obtained in the same manner as in Example 1, except that the water washing treatment time was as shown in Table 1-2.
[0115] [Examples 21 to 23] A polyester resin was obtained in the same manner as in Example 6, except that the water washing treatment time was as shown in Table 1-2.
[0116] [Example 24] A polyester resin was obtained in the same manner as in Example 1, except that the sodium hydroxide concentration, contact time with the alkaline treatment liquid, and water washing treatment time were as shown in Table 1-2.
[0117] [Example 25] A polyester resin was obtained in the same manner as in Example 6, except that the sodium hydroxide concentration, contact time with the alkaline treatment liquid, and water washing treatment time were as shown in Table 1-2.
[0118] [Example 26] A polyester resin was obtained in the same manner as in Example 1, except that the alkaline treatment liquid was changed to 3% by mass of potassium hydroxide.
[0119] [Example 27] A polyester resin was obtained in the same manner as in Example 6, except that the alkaline treatment liquid was changed to 3% by mass of potassium hydroxide.
[0120] [Comparative Examples 1 and 2] A polyester resin was obtained in the same manner as in Example 1 except that the contact time with the alkaline treatment liquid was set as shown in Table 2.
[0121] [Comparative Examples 3 and 4] A polyester resin was obtained in the same manner as in Example 6 except that the contact time with the alkaline treatment liquid was set as shown in Table 2.
[0122] [Comparative Examples 5 and 6] A polyester resin was obtained in the same manner as in Example 1, except that the sodium hydroxide concentration was as shown in Table 2.
[0123] [Comparative Examples 7 and 8] A polyester resin was obtained in the same manner as in Example 6 except that the sodium hydroxide concentration was as shown in Table 2.
[0124] [Comparative Examples 9 and 10] A polyester resin was obtained in the same manner as in Example 1, except that the water washing treatment time shown in Table 2 was used.
[0125] [Comparative Example 11] A polyester resin was obtained in the same manner as in Example 6, except that the water washing treatment time shown in Table 2 was used.
[0126] [Comparative Example 12] A polyester resin was obtained in the same manner as in Example 1, except that the sodium hydroxide concentration, contact time with the alkaline treatment liquid, and water washing treatment time were as shown in Table 2.
[0127] [Comparative Example 13] A polyester resin was obtained in the same manner as in Example 6, except that the sodium hydroxide concentration, contact time with the alkaline treatment liquid, and water washing treatment time were as shown in Table 2.
[0128] [Comparative Example 14] A polyester resin was obtained in the same manner as in Example 1. When evaluating the adhesion of the release layer of the laminated recycled polyester film, the thickness ratio of the laminated recycled polyester film was set to A layer / B layer / A layer=3 μm / 19 μm / 3 μm.
[0129] [Table 1-1]
[0130] [Table 1-2]
[0131] [Table 2]
[0132] As shown in Table 1, in the case of the polyester resin of the present invention, it was confirmed that the color tone of the polyester resin, foreign matter, and adhesion of the release layer of the film using the polyester resin of the present invention and the laminated recycled polyester film were good.
[0133] In contrast, polyester resins having Si contents or alkali metal contents outside the range specified in the present invention have poor color tone, foreign matter, and adhesion of the release layer of films using the polyester resin of the present invention or laminated recycled polyester films, and it is expected that it will be difficult to remake this polyester resin into a film, coat it with a functional layer such as a release layer, and use it as a variety of industrial materials. As described above, the polyester resin of the present invention has a good color tone, contains little foreign matter, and has good adhesion to the functional layer, and is expected to be usable as a variety of industrial materials.
Claims
1. A recycled polyester resin that satisfies the following requirements 1) and / or 2). 1) The recycled polyester resin has a Si content of 0.5 mmol% or more and 27.3 mmol% or less. 2) The amount of alkali metal in the recycled polyester resin is 0.5 mmol% or more and 20.0 mmol% or less.
2. 2. The recycled polyester resin according to claim 1, which is produced by removing a release layer mainly made of silicone from a polyester film.
3. The recycled polyester resin according to claim 2, wherein the release layer is removed by a roll-to-roll method.
4. A laminated recycled polyester film consisting of at least three layers, including a polyester layer A (A layer) having a film surface, and a C layer containing a recycled polyester resin satisfying the following requirements 3) and / or 4) and having no film surface. 3) The recycled polyester resin has a Si content of 0.5 mmol% or more and 27.3 mmol% or less. 4) The amount of alkali metal in the recycled polyester resin is 0.5 mmol% or more and 20.0 mmol% or less.
5. 5. A laminated recycled polyester film, the recycled polyester resin according to claim 4 being produced by removing a release layer mainly composed of silicone from a polyester film.
6. 6. The laminated recycled polyester film according to claim 5, wherein the release layer is removed by a roll-to-roll method.
Citation Information
Patent Citations
Recovering method for photographic polyester base
JP1996146560A
Method of cleaning release film and method of recycling base film and release film
JP2009291690A
Method for removing functional layer from base film having functional layer, and method for collecting base film
JP2020090094A
Laminated film and functional layer removal method
JP2023020615A